Soil quality attributes related to urbanization in Brazilian watershed - Silva, Alexandre Marco da; Urban, Rodrigo Custodio; Manfré, Luiz Augusto; Brossard, Michel; Moreira, Marcelo Zacharias (Journal of Environmental Engineering and Landscape Management, 2017)
In this study we investigated the variation of soil attributes according to urban-related land cover categories. The study was carried out in an urbanized watershed located in the Brazilian subtropical region (Sorocaba Municipality, São Paulo). Soil samples were collected considering the land cover category for analysis of physical, chemical and isotopic attributes. The land cover influenced the soils attributes. Soils from wooded and grassed areas presented significant differences, especially for values of C isotopes. Soil bulk density was significantly altered. According to considered land cover mosaic in the study, we estimated 10,241.28 tons of C stored in the thickness 20 cm of the watershed (whole area), and this amount is almost a half of the total potential of C storing in the watershed. We stress that projects of planned land cover should effectively implemented in urbanized regions to effectively contribute in storing more C and improving the soil-related ecosystem services.